2018
DOI: 10.1111/ijd.14140
|View full text |Cite
|
Sign up to set email alerts
|

White and yellow dots as new trichoscopic signs of severe female androgenetic alopecia in dark skin phototypes

Abstract: The yellow dot and white dot signs are suggested as new dermoscopic findings in advanced androgenetic alopecia. Peripilar sign, honeycomb pigmentation, and white dots are characteristic signs of female androgenetic alopecia in ethnic groups of darker skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 21 publications
3
21
1
Order By: Relevance
“…Compatible to our study, Rakowska et al reported that 65% (39/59) of AGA patients had single‐hair pilosebaceous unit and Tawfik et al demonstrated that 97.4%(77/79) of AGA patients had single‐hair pilosebaceous unit on the frontal scalp.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Compatible to our study, Rakowska et al reported that 65% (39/59) of AGA patients had single‐hair pilosebaceous unit and Tawfik et al demonstrated that 97.4%(77/79) of AGA patients had single‐hair pilosebaceous unit on the frontal scalp.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies as reported higher percentages than our study (63% and 83%), respectively. Tawfik et al suggested that this disparity in findings could be explained by the difference in ethnic group enrolled in the previous studies. Another cause of such disparity is the removal of the accumulated sebum by washing hair.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations